Webtoon Media with Problem-Based Learning Model in Improving Elementary School Science Learning Outcomes - Ni Putu Nita Loka; I Made Citra Wibawa; Luh Putu Sri Lestari (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes in IPAS (Science and Social Education) among elementary school students are attributed to the lack of problem-based learning and the absence of innovative learning media, leading to reduced student engagement during the learning process. This study aims to develop and evaluate the validity, practicality, and effectiveness of webtoon-based learning media integrated with the Problem-Based Learning (PBL) model to improve students' learning outcomes in IPAS. The research employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The participants included fourth-grade students and a classroom teacher. Data were collected through interviews, questionnaires, and achievement tests, and analyzed using qualitative methods, descriptive quantitative analysis, and inferential statistics. The results show that: (1) the webtoon media was developed using the IbisPaint application aligned with PBL principles; (2) the validity scores were 3.76 (content expert) and 3.85 (media expert), both categorized as highly valid; (3) the practicality scores reached 96.1% from teachers and 96.8% from students; and (4) the media’s effectiveness was demonstrated through an average n-gain of 89.5 and a learning mastery percentage of 89.5%. These findings indicate that the webtoon-based learning media integrated with the PBL model is valid, practical, and effective for enhancing students’ IPAS learning outcomes. This study highlights the potential of interactive visual media to support innovative and meaningful learning in elementary education.